PERBANDINGAN VALIDITAS FLACC SCALE DAN NIPS DALAM PENILAIAN NYERI AKUT PADA INFANT - Desi " Wahyuni; Riri " Novayelinda; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this study was to compare the validity of pain scales between FLACC Scale and NIPS in acute pain of 22 infants at mandau General Hospital. This study was an observational analitical study toward diagnostic test. Thisstudy design was cross-sectional with nonprobability sampling using purposive sampling method. CRIES was used as the gold-standard. The data were analysed by using concurrent validity, sensitivity-specificity, and Receiver Operating Characteristic (ROC) curve. In concurrent validity analysis showed FLACC Scale and NIPS has a positive correlation was almost as strong against the gold standard (r =, 578: r =, 557). FLACC Scale also had a sensitivity of 100% and specificity of 44%, which is almost the same with NIPS (sensitivity 100%, specificity 50%). In the ROC curve analysis, obtained the Area under the Curve (AUC) for the scale FLACC Scale (89.6%) were also similar to the AUC values at NIPS (88.9%). The results of this study concluded that pain measurement tool using FLACC Scale and NIPS has a degree of validity that are statistically equally well in assessing infant acute pain that is expected to be a reference in the assessment of pain in infants. Keyword: infant, acute paint,  FLACC scale, NIPS, validity.